Differential effects of word length and visual contrast in the fusiform and lingual gyri during reading. - Mechelli, A; Humphreys, G; Mayall, K; Olson, A; Price, C (2000)
Previous studies have shown differential responses in the fusiform and lingual gyri during reading and suggested that the former is engaged in processing local features of visual stimuli and the latter is engaged in global shape processing. We used positron emission tomography in order to investigate how these regions are modulated by two common variables in reading: word length (three, six and nine letters) and perceptive similarity to the background (high and low contrast). Increasing both word length and visual contrast had a positive monotonic effect on activation in the bilateral fusiform. However, in the lingual gyrus, activation increased with increasing word length but decreased with increasing contrast. On the basis of previous studies, we suggest that (i) increasing word length increases the demands on both local feature and global shape processing, but (ii) increasing visual contrast increases the demands on local feature processing while decreasing the demands on global shape processing.